Therapeutic Modulation of Growth Factors and Cytokines in Regenerative Medicine - Ioannidou, Effie (Current Pharmaceutical Design, 2006)
Regeneration that takes place in the human body is limited throughout life. Therefore, when organs are irreparably damaged, they are usually replaced with an artificial device or donor organ. The term
Keywords: cytokines